2014
DOI: 10.1007/s00467-014-2949-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of everolimus on tuberous sclerosis-associated lesions can be dramatic but may be impermanent

Abstract: While everolimus provides a non-invasive way to treat TSC-associated lesions, patients may require lifelong therapy. When termination of therapy is considered, the patient should be made aware of the expectation of potentially dramatic increases in lesion size. If consideration is to be given to definitive surgical therapy, it should be pursued while the patient is still on the medication, or at least soon after treatment is halted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…As mentioned previously, limited data suggest that mTOR inhibitors may require continuous use to maintain reductions in TSC‐associated tumors 11, 12. In our study, regrowth of SEGA was observed in 1 patient who had previously met the criteria for treatment success (75% reduction in SEGA volume) at 18 months and then discontinued everolimus.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As mentioned previously, limited data suggest that mTOR inhibitors may require continuous use to maintain reductions in TSC‐associated tumors 11, 12. In our study, regrowth of SEGA was observed in 1 patient who had previously met the criteria for treatment success (75% reduction in SEGA volume) at 18 months and then discontinued everolimus.…”
Section: Discussionsupporting
confidence: 61%
“…In some cases discontinuation of mTOR inhibition has resulted in regrowth of TSC‐associated lesions 11, 12. For example, a study evaluating an mTOR inhibitor in treating angiomyolipomas, the renal tumors associated with TSC, demonstrated regrowth of lesions in several patients nearly to baseline 1 year after cessation of mTOR treatment 12.…”
mentioning
confidence: 99%
“…Volumetric findings derived by RT3DE documented relevant shrinking of the LV tumor's size after 19 days of treatment. Although rebound growth of mTOR sensitive tumors following discontinuation of treatment has been reported, there is no growing tendency in the presented case in a 5‐month follow‐up interval.…”
Section: Discussionmentioning
confidence: 55%
“…The authors decided to modify previously used everolimus treatment regimes for RHM . By once‐daily drug dosing, close drug monitoring, and adjustments, it was believed to deliver therapeutic levels that would avoid toxicity and ensure anti‐proliferative effects on the targeted tissue in accordance with the treatment for SEGA . Despite the authors observed high trough levels in the initial dosage finding process, no severe side effects were seen besides slightly elevated triglycerides and transitory lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, the isolated lung and brain lesions resolved after discontinuation of sirolimus, which is contrary to that reported by Miller and associates, who showed marked improvement rather than deterioration with mTORi administration. 14 Sarcoidosis could be considered as an important differential diagnosis in this case, especially in the absence of infections, presence of lymph nodes, and multisystem effects. 15 However, a lack of bilateral lymph nodes in the lungs, absence of granuloma, and normal angiotensin-converting enzyme level and disease development in the presence of maintenance immunosuppressive drugs can exclude this important diagnosis.…”
Section: Discussionmentioning
confidence: 99%